If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13 + -7x = -1(5 + -11x) 13 + -7x = (5 * -1 + -11x * -1) 13 + -7x = (-5 + 11x) Solving 13 + -7x = -5 + 11x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-11x' to each side of the equation. 13 + -7x + -11x = -5 + 11x + -11x Combine like terms: -7x + -11x = -18x 13 + -18x = -5 + 11x + -11x Combine like terms: 11x + -11x = 0 13 + -18x = -5 + 0 13 + -18x = -5 Add '-13' to each side of the equation. 13 + -13 + -18x = -5 + -13 Combine like terms: 13 + -13 = 0 0 + -18x = -5 + -13 -18x = -5 + -13 Combine like terms: -5 + -13 = -18 -18x = -18 Divide each side by '-18'. x = 1 Simplifying x = 1
| 13-7x=5-11x | | 25=5(a-7) | | 5v-18=10v-53 | | 3(-5x-17)=3 | | 2(4y)-y=-1 | | 8-3=2(x+1) | | B=3/4(21-b) | | (n+7)(11n-2)=18n(2n+1) | | A=21-b | | 4/3(-5.25) | | f(4)=2.0x^2+7.6x^4+5.0 | | f(x)=2.0x^2+7.6x^4+5.0 | | F=5(10)+18 | | 9w+(-31)= | | 11n^2+21n-14=0 | | -9/5x=27 | | q=m*c*changeT | | F=5(4)+18 | | F=5(2)+18 | | X+5a=29+ax-6a | | 2n=-28n-3 | | V=XLT | | 2x-x+112=16x+112 | | 3/e=3/4 | | 5n-6=18 | | 2y-3+y+6=12 | | F=5(3)+11 | | F=5(5)+11 | | 2x+8x+4+x=180 | | 2q+2q-48=180 | | 3d=15d | | F=14(4)+18 |